Proceedings of the 25th International Symposium on Software Testing and Analysis 2016
DOI: 10.1145/2931037.2931065
|View full text |Cite
|
Sign up to set email alerts
|

Zero-overhead profiling via EM emanations

Abstract: This paper presents an approach for zero-overhead profiling (ZOP). ZOP accomplishes accurate program profiling with no modification to the program or system during profiling and no dedicated hardware features. To do so, ZOP records the electromagnetic (EM) emanations generated by computing systems during program execution and analyzes the recorded emanations to track a program's execution path and generate profiling information. Our approach consists of two main phases. In the training phase, ZOP instruments t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 41 publications
(43 reference statements)
0
14
0
Order By: Relevance
“…These developmental options affect the performance of the software being inspected in addition to the overhead of their placement each time a copy of the software needs to be inspected. It has been shown that unintended EM emissions of the CPU can be used to inspect software execution sequences without having to instrument the software [48,49,50,51]. Even when the same program is running on different devices, the ability to identify the instruction execution sequence can help to uniquely identify the software itself.…”
Section: Electromagnetic Emissions As a Software Signaturementioning
confidence: 99%
“…These developmental options affect the performance of the software being inspected in addition to the overhead of their placement each time a copy of the software needs to be inspected. It has been shown that unintended EM emissions of the CPU can be used to inspect software execution sequences without having to instrument the software [48,49,50,51]. Even when the same program is running on different devices, the ability to identify the instruction execution sequence can help to uniquely identify the software itself.…”
Section: Electromagnetic Emissions As a Software Signaturementioning
confidence: 99%
“…Recently, there has been a push towards using EMI to profile code. Callan et al [5] proposed ZOP: a zero-overhead approach to obtain profiling information via EMI measurements. ZOP first goes through a training phase in which it builds a model that associates different wave forms with different parts of the code.…”
Section: Profilingmentioning
confidence: 99%
“…MESC takes into account the activity rate of individual wires in a process and the layout to approximate the expected EMI from that process. This is in distinct contrast to previous works that utilize measured EMI to profile programs [5,19] or to isolate the on-chip location of magnetic field sources [25], as we aim to model the EMI from the layout, not the other way around. MESC uses some basic initial power measurements of a device as well as statistical sampling of switching activity in order to model the expected EMI of a processor.…”
Section: Introductionmentioning
confidence: 98%
“…Interest in tracking the program activity is drawing the attention of experts from various fields due to its possible applications in monitoring code flow, detecting malicious activities, reverse engineering, cryptanalysis, etc. [1][2][3][4][5][6][7] Side channels are unintentional and asynchronous channels that can leak some sensitive information while performing a computer activity. 8 Many attacks are reported based on power analysis, 1, 2, 9-11 temperature analysis, 12 acoustic emanations, 13,14 electromagnetic (EM) emanations, 7,[15][16][17][18] etc.…”
Section: Introductionmentioning
confidence: 99%
“…One of the emerging applications of side-channel analysis is their use for tracking program activities on various code levels such as loops, paths, and basic blocks. [3][4][5][6]19 Most of the previous work on single instruction code analysis is focused on building sidechannel-based disassembler, 1,20,21 i.e. reconstructing the instructions from the side-channel signal.…”
Section: Introductionmentioning
confidence: 99%